2020
DOI: 10.3389/fpsyg.2020.02037
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Trends Inside Sport: When Organized Sport Does Not Attract but Intimidates

Abstract: Bullying is acknowledged by scientists as a considerable and still unresolved problem in sport. By triggering stress-related emotions, they determine the behavior of those experiencing bullying and cause various negative effects on their physical and mental health. However, in the presence of the tenacious trend in sports “to put one’s own house in order,” athletes, coaches, teams, and sports organizations themselves often do not emphasize bullying or state that they do not encounter the problem at all, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
1
10
1
2
Order By: Relevance
“…Families do not have clear indications of how to act when a case of bullying occurs, reason why it would be necessary to promote their training ( Flores et al, 2020 ). On the other hand, the coach becomes one of the key agents, since they can act as a role model or mentor and promote, maintain or inhibit bullying ( Nery et al, 2020 ; Vveinhardt and Fominiene, 2020 ). The victims perceived that the coach had little interest in personal experiences, giving little importance to the interpersonal relationships created in the athletes’ group and, at the same time, trivializing the situations of conflict that could arise, focusing their intervention in merely sporting elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families do not have clear indications of how to act when a case of bullying occurs, reason why it would be necessary to promote their training ( Flores et al, 2020 ). On the other hand, the coach becomes one of the key agents, since they can act as a role model or mentor and promote, maintain or inhibit bullying ( Nery et al, 2020 ; Vveinhardt and Fominiene, 2020 ). The victims perceived that the coach had little interest in personal experiences, giving little importance to the interpersonal relationships created in the athletes’ group and, at the same time, trivializing the situations of conflict that could arise, focusing their intervention in merely sporting elements.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of teacher-student relationship can lead victims to stop reporting the event due to a perception of indifference from the teacher, or due to the feeling that they will not solve the problem positively ( Nery et al, 2020 ). Therefore, the actions taken by the coaches did not favor, in general, putting an end to bullying, probably due to a lack of education and knowledge about this phenomenon ( Kowalski, 2017 ; Flores et al, 2020 ) and due to their education being focused on athletic performance, with traditional training styles ( Vveinhardt and Fominiene, 2020 ), creating a high pressure environment for the victim ( Vveinhardt et al, 2017 ). Thus, it is advisable to increase the knowledge on the subject by the coaches and articulate pedagogic dynamics that are in line with the athletes’ youth sport training ( Collot and Dudink, 2010 ; Baar and Wubbels, 2013 ; Shannon, 2013 ; Nery et al, 2019 ; Flores et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrimo tikslui, susijusiam su sportinės veiklos organizavimo ypatumais COVID-19 pandemijos metu, pasiekti empiriniame tyrime pasirinkta kokybinio tyrimo tradicija, kadangi ji siejasi su tikslu suprasti bei atskleisti asmenį supančią socialinę tikrovę per žmogaus patirtis (Vveinhardt, Fominiene, 2020).…”
Section: Metodikaunclassified
“…As is reflected by [ 5 ], bullying is one of the subsets of social aggression that started to be analysed more extensively 40 years ago and, in the last decade, attracted increasing interest from researchers in various countries, which is still ongoing to this day [ 6 ]. In this context, bullying is relevant as it is produced in the educational environment, where its consequences can have a significant impact [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [ 6 , 24 ] have linked an environment of physical education (PE) to bullying acts. In this sense, it has been suggested that victims of school bullying tend to avoid school contexts that make them feel vulnerable, among which the authors highlight those found in physical activities [ 25 ].…”
Section: Introductionmentioning
confidence: 99%